The Training System of Sufism in the Light of Maktubat-e-Mujaddidiya: An Analytical Study - Dr. Wajahat Khan; Dr. Naveed Altaf Khan (Journal of Religion and Society, 2025)
The system of spiritual training presented in the Maktubat of Imam Rabbani, Shaykh Ahmad Sirhindi (Mujaddid Alf Thani), is a comprehensive and structured model for the moral and spiritual development of the human self. The objective of this Sufi methodology is to free the soul from the dominance of nafs (base desires) and guide it towards the pleasure of Allah Almighty. This system is firmly rooted in adherence to Shariah, constant remembrance of Allah (dhikr), renunciation of dunya (worldlya attachment), and the companionship of a perfect spiritual guide (Shaykh Kamil). Imam Rabbani emphasised that true spiritual refinement lies in inner purification (tazkiyah al-nafs), which leads a seeker (salik) to proximity with the Divine (qurb Ilahi). This paper explores the core principles of Mujaddid Alf Thani’s training methodology, including self-purification, avoidance of worldly love, the centrality of dhikr in spiritual healing, and the significance of the Shaykh–disciple (murid) relationship. It highlights how his system begins from the ‘Alam al-Amr (metaphysical world) rather than the ‘Alam al-Khalq (physical world), placing spiritual attraction (jadhbah) above disciplined effort (suluk). The concept of khalwat dar anjuman (solitude in the crowd) reflects the balanced integration of spiritual focus and social engagement. His teachings call for strict adherence to the Sunnah and a firm rejection of bid‘ah (innovations) in religious practices. The study concludes with key suggestions for further research, such as simplifying the language of the Maktubat for wider accessibility, reorganising the letters thematically for ease of study, and codifying their spiritual guidance in a structured legal-like format to assist seekers (salikin) and researchers alike. Keywords: Imam Rabbani, Maktubat, spiritual training, Sufism, tazkiyah al-nafs, dhikr, Shaykh Kamil, suluk, jadhbah, khalwat dar anjuman, nafs, Shariah, Sunnah, bid‘ah, salik, murid, Islamic spirituality, inner purification, Mujaddid Alf Thani, spiritual methodology